Launch of the book „Under four regimes on all continents” by Alexandru Budişteanu or Chronicle of a generation (Confluenţe Bibliologice, 2025)
The author proposes to release a retrospective volumes of memoirs „Under four regimes on all continents“, written by Dr. Architect Alexandru Budişteanu, Member of the Scientiﬁc Council of the National Institute for the study of Totalitarianism (INST) of the Romanian Academy, President Emeritus of the English-Speaking International Union of Romania brunch.(ESU) the title of „Doctor Honoris Causa” of the State University „Alecu Russo” of Balti, Republic of Moldova, the title of Oﬃcer of the Order of the Faithful Service of Romania (OFS), President of Cultural Foundation „Alexandru Budisteanu”. The event was held at USARB Scientiﬁc Library. The book renders a fascinating history of the high school pupil world from Bălţi who lived a life marked by various events in the 20th and 21st centuries, has come to be a valuable intellectual, a model for today’s young people, including students along with teachers, librarians and other guests will keep in memory this hour of patriotism and great love of Alma Mater Liceym „Ion Creanga” from Balti.
Keywords: Budişteanu Alexandru (1928-2021); Romanian history